PENGARUH ASUPAN SAYUR KANGKUNG (IPOMEA REPTANS POIR.) DAN OLAHRAGA RENANG TERHADAP INTENSITAS KECEMASAN PADA REMAJA LAKI-LAKI The Eﬀect of Kangkong Vegetables (Ipomea reptans Poir.) and Swimming on Anxiety Intensity in Adolescent Male - Sigit Yudhistira; Adi Magna Patriadi Nuhriawangsa; Mohammad Fanani (Universitas Airlangga, 2021)
High stress levels in adolescents can cause mental health disorders such as anxiety. Kangkong vegetables has nutrients superior in reducing anxiety, in 250 grams of kangkong vegetables contains carbohydrates (9,7 g), vitamin B1 (0,17 mg), vitamin C (42,5 mg), calcium (167,5 mg), zinc (1 mg), iron (5,7 mg), potassium (625,2 mg), sodium (162,5 mg), flavonoids, alkaloids and steroids for metabolism and increased hormone in the brain such as BDNF, GABA, serotonin, dopamine and norepinephrine which reduce anxiety. Swimming has superior as a recreational eﬀort in reducing anxiety, also keeps the body fit and relaxed for metabolism and increased hormones in the brain such as BDNF, GABA, serotonin, dopamine and norepinephrine which reduce anxiety. The purpose of this study was to analyze the eﬀect of kangkong vegetables and swimming in the intensity of anxiety in adolescent. The study uses a quasi-experimental study design pre-post test control group design, involving 61 male students, taken from 3 senior high schools and grouped into 3: control group by giving swimming 2 times / week for 2 weeks (pool depth 120 cm and swimming duration for 60 minutes / exercise) (P0) (n=22), group by giving 250 grams of kangkong vegetables / day for 14 days (divided into 2) (P1) (n=19) and group by giving combination of kangkong vegetables and swimming (P2) (n=20). The results of the study used the ANOVA, the decrease in anxiety intensity in all groups not much diﬀerent from the value (p=0.593). The conclusion this study is the giving of kangkong vegetables, swimming can reduce the intensity of anxiety in adolescent male.